KONTRIBUSI KOMPETENSI SUPERVISI KEPALA SEKOLAH TERHADAP PELAKSANAAN TUGAS GURU SMP NEGERI KECAMATAN PADANG TIMUR - Reni Seprina (Jurnal Bahana Manajemen Pendidikan, 2013)
This research is motivated from the observation writers District Junior High School in Padang Timur Padang city which shows the performance of duties of teachers is still low.It is thought to be related to the competence of the principal supervision, because supervision is implemented will not affect the implementation of the optimal assignment the teacher. This study aims to view its supervisory competence contribute significantly to the performance of duties of teachers. Population of teachers who 273 people and 56 samples were taken with the Proportional stratified random sampling technique. The research instrument was a Likert scale questionnaire form which has been in testing the validity and reliable. To test the hypothesis using a simple regression analysis, the formula Product Moment, Test and Test-r-t, while r ² is used to look at the contribution of the principal's competency supervision duties of teachers. The results are quite good supervision competence and task execution was pretty good teacher and great contribution of variable competence of the principal supervision of the implementation of the teacher's task is 29.16%, while the remaining 70.84% is influenced by other factors. Kata kunci: kompetensi supervisi dan pelaksanaan tugas